Turmeric and Its Major Compound Curcumin on Health: Bioactive Effects and Safety Profiles for Food, Pharmaceutical, Biotechnological and Medicinal Applications - Sharifi-Rad, Javad; Rayess, Youssef El; Rizk, Alain Abi; Sadaka, Carmen; Zgheib, Raviella; Zam, Wissam; Sestito, Simona; Rapposelli, Simona; Neffe-Skocińska, Katarzyna; Zielińska, Dorota; Salehi, Bahare; Setzer, William N.; et al. (Frontiers in Pharmacology, 2020)
Curcumin, a yellow polyphenolic pigment from the Curcuma longa L. (turmeric) rhizome, has been used for centuries for culinary and food coloring purposes, besides to be an ingredient for various medicinal preparations and widely used in Ayurveda or Chinese medicine. In the last decades, their biological activities have been extensively studied. Thus, the focus of this review is to offer an in-depth revision of curcumin applications for food and biotechnological industries, on health promotion and disease prevention, with emphasis on its antioxidant, anti-inflammatory, neuroprotective, anticancer, hepatoprotective, and cardioprotective effects. Bioavailability, bioefficacy, safety, side effects and quality parameters of curcumin are also focused. Finally, curcumin’ multidimensional applications, food attractiveness optimization, agroindustrial procedures to offset its instability and low-bioavailability, health concerns and upcoming strategies and clinical application were also covered.